2016
DOI: 10.1038/srep25602
|View full text |Cite
|
Sign up to set email alerts
|

miRNA let-7b modulates macrophage polarization and enhances tumor-associated macrophages to promote angiogenesis and mobility in prostate cancer

Abstract: Macrophage polarization is a highly plastic physiological process that responds to a variety of environmental factors by changing macrophage phenotype and function. Tumor-associated macrophages (TAMs) are generally recognized as promoting tumor progression. As universal regulators, microRNAs (miRNAs) are functionally involved in numerous critical cellular processes including macrophage polarization. Let-7b, a miRNA, has differential expression patterns in inflamed tissues compared with healthy controls. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 49 publications
4
63
0
Order By: Relevance
“…When addressing the “exclusive lung interactions” the genes CDT1, CENPN, DAPK2, HJURP, KIF20A, NACPD2, NCAPG, NCAPH, SMC1B , and SPC24 have so far not been associated to survival in lung cancer, although most of its associated miRNAs have been. For instance miR-miR-1976 and miR-let-7b-5p miRNAs had already been associated to prognosis in lung cancer4969, and in other tumours like breast70, prostate71, and gastric72. In conclusion, our analysis has revealed novel miRNA-gene correlations that associate with patient prognosis, supported by previous findings on different tumour types.…”
Section: Discussionsupporting
confidence: 87%
“…When addressing the “exclusive lung interactions” the genes CDT1, CENPN, DAPK2, HJURP, KIF20A, NACPD2, NCAPG, NCAPH, SMC1B , and SPC24 have so far not been associated to survival in lung cancer, although most of its associated miRNAs have been. For instance miR-miR-1976 and miR-let-7b-5p miRNAs had already been associated to prognosis in lung cancer4969, and in other tumours like breast70, prostate71, and gastric72. In conclusion, our analysis has revealed novel miRNA-gene correlations that associate with patient prognosis, supported by previous findings on different tumour types.…”
Section: Discussionsupporting
confidence: 87%
“…Among the members of the let-7 family, let-7b and let-7f promote angiogenesis by suppressing two important inhibitors of cellular migration: Tissue inhibitor of metalloproteinase 1 (TIMP-1) and Tsp 1 and 2 [66,67]. In prostate cancer, let-7b regulates macrophage polarization and enhances tumor-associated macrophages to stimulate angiogenesis by modulating the expression profile of inflammatory cytokines such as interleukin (IL)-12, IL-23, IL-10, and tumor necrosis factor-α [68].…”
Section: Lethal (Let)-7b and -7fmentioning
confidence: 99%
“…Our previous study showed that let-7b is highly expressed in M-CMs, which have an M2-like phenotype 20 .…”
Section: Discussionmentioning
confidence: 98%
“…Our previous results indicated that conditioned media from PC-3 PCa cells can induce macrophages to differentiate into M2 macrophages, a process that is signi cantly associated with the high expression of let-7 20 . Therefore, we focused on let-7b-5p targeting SOCS1/STAT in macrophages and its role in the progression of PCa.…”
Section: Introductionmentioning
confidence: 96%